2016
DOI: 10.1007/s00384-016-2687-2
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of subcutaneous closed-suction Blake drains for the prevention of incisional surgical site infection after colorectal surgery

Abstract: The results of our RCT suggest that a subcutaneous Blake drain is beneficial for preventing incisional SSIs in patients undergoing colorectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…Logistic regression analysis demonstrated that thickness of subcutaneous fat > 3.0 cm, forced expiratory volume in 1 s as percent of forced vital capacity (FEV1.0%) > 70%, and subcutaneous drain were independent predictors of postoperative incisional SSIs (P = 0.008, P = 0.004, and P = 0.017, respectively). The authors affirmed that a subcutaneous Blake drain is beneficial for preventing incisional SSIs in patients undergoing colorectal surgery [76].…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Logistic regression analysis demonstrated that thickness of subcutaneous fat > 3.0 cm, forced expiratory volume in 1 s as percent of forced vital capacity (FEV1.0%) > 70%, and subcutaneous drain were independent predictors of postoperative incisional SSIs (P = 0.008, P = 0.004, and P = 0.017, respectively). The authors affirmed that a subcutaneous Blake drain is beneficial for preventing incisional SSIs in patients undergoing colorectal surgery [76].…”
Section: Resultsmentioning
confidence: 94%
“…Recently, Watanabe et al [76] decided to evaluate the effects of subcutaneous closed-suction Blake drain for preventing SSIs after colorectal surgery performing an RCT, enrolling 240 patients. The incidence of incisional SSI was 8.7% in the overall patients.…”
Section: Resultsmentioning
confidence: 99%
“…In general, some factors such as smoking, obesity, and diabetes mellitus are reported as risk factors for SSI occurrence [9,19] but in elective surgery, countermeasures such as smoking cessation or weight reduction may also be considered; however, it is difficult in emergency surgery. In colorectal surgery, the left-side colon and stoma creation are also mentioned [17,20]; however, taking measures specifically for each disease is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In cases with subcutaneous fat tissue of > 20 mm in colorectal emergency surgery, SSI has been improved from 39 to 14% by placing a subcutaneous drain. In addition, Watanabe et al [9] reported that subcutaneous drainage effectively prevented incisional SSI in their RCT on 200 cases of colorectal surgery. Conversely, Baier et al [22] reported that subcutaneous drainage has no effect on incisional SSI in their RCT with the same number of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation